Ecological and human-induced factors driving the invasion of Neurada procumbens in a protected coastal dune ecosystem: insights from chorological analysis within an environmental management framework - Emilio Medina-Lorenzo; Antonio I. Hernández-Cordero; Abel Sanromualdo-Collado; Leví García-Romero (Journal of Environmental Management, 2026)

What strategies would sheep farmers implement to respond to climate change? A cross-national comparison of sheep farming systems in the Mediterranean - D. Martin-Collado; A. Tenza-Peral; I. Casasús; M. Joy; F. Stark; A. Lurette; A. Mohamed-Brahmi; M. Ameur; A. Aboulnaga; M. Elshafie; S. Lobón (Small Ruminant Research, 2025)

Indicators of geomorphological connectivity facing management fragmentation in coastal protected areas: the case of Guguy (Canary Islands) - Abel Sanromualdo-Collado; Nicolás Ferrer; Néstor Marrero-Rodríguez; Antonio I. Hernández-Cordero; Leví García-Romero (Ocean & Coastal Management, 2025)

Under threat: Land use change, distribution and conservation of poorly-known endemic microsnails from the coast of Chile - Gonzalo A. Collado; Juan Francisco Araya; Viviana Castillo; Nicolás I. Villalobos (Anthropocene, 2025)

Dual-Curing MWCNT nanocomposites for Energy-Efficient electroactive shape memory and In-Situ processing - I. Collado; A. Vázquez-López; A. Jiménez-Suárez; S.G. Prolongo (Chemical Engineering Journal, 2025)

Assessing the temporal isolation barrier between two closely related species of the genus Fissurella off the southwestern coast of South America - Gonzalo A. Collado; Selva L. Luna; Donald I. Brown (Invertebrate Reproduction & Development, 2024)

“Alstroemeria maxima (Alstroemeriaceae, Alstroemerieae), a hidden giant” revealed through integrative taxonomy - Nicolás I. Villalobos; Carlos M. Baeza; Víctor L. Finot; Óscar Toro-Núñez; Eduardo Ruiz-Ponce; Koji Takayama; Hiroshi Noda; Gonzalo A. Collado; Freddy Mora-Poblete (Brazilian Journal of Botany, 2024)

Is temperature change a key driver of the regional differences in electricity consumption of the economic sectors in Spain (2000–2016)? - Rocío Román-Collado; María J. Colinet-Carmona; María I. Fárez-Plasencia (Environmental Science and Pollution Research, 2023)
Climate change has caused significant changes in temperature with different consequences depending on the geographical location of the regions, affecting among other aspects, electricity consumption (EC). Spain being a country that encompasses so many different temperature zones, this work analyses EC per capita among the Autonomous Communities (AC) of Spain through a spatial-temporal decomposition analysis during the 2000–2016 period. The regional differences are explained by four decomposition factors: intensity, temperature, structural and per capita income. The temporal decomposition results show that temperature changes in Spain between 2000 and 2016 have substantially affected the per capita EC. Likewise, it has been noted that in the 2000–2008 period, the temperature effect mainly acted as an inhibitor compared to the 2008–2016 period, in which an increase in the days of extreme temperature acted as a driver. The spatial decomposition reveals that the structural and energy intensity effects contribute to the AC moving away from average figures, while the temperature and income effects contributes to reducing the differences depending on the location of the AC. The results enable to determine the importance of establishing public policy measures aimed at improving energy efficiency.

Diversity of the holopelagic Sargassum microbiome from the Great Atlantic Sargassum Belt to coastal stranding locations - Tom Theirlynck; Inara Regina W. Mendonça; Aschwin H. Engelen; Henk Bolhuis; Ligia Collado-Vides; Brigitta I. van Tussenbroek; Marta García-Sánchez; Erik Zettler; Gerard Muyzer; Linda Amaral-Zettler (Harmful Algae, 2023)

Multiple late‐Pleistocene colonisation events of the Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae) reveal the recent arrival of native Antarctic vascular flora - Elisabeth M. Biersma; Cristian Torres‐Díaz; Marco A. Molina‐Montenegro; Kevin. K. Newsham; Marcela A. Vidal; Gonzalo A. Collado; Ian S. Acuña‐Rodríguez; Gabriel I. Ballesteros; Christian C. Figueroa; William P. Goodall‐Copestake; Marcelo A. Leppe; Marely Cuba‐Díaz; et al. (Journal of Biogeography, 2020)
Aim Antarctica's remote and extreme terrestrial environments are inhabited by only two species of native vascular plants. We assessed genetic connectivity amongst Antarctic and South American populations of one of these species, Colobanthus quitensis , to determine its origin and age in Antarctica. Location Maritime Antarctic, sub‐Antarctic islands, South America. Taxon Antarctic pearlwort Colobanthus quitensis (Caryophyllaceae). Methods Four chloroplast markers and one nuclear marker were sequenced from 270 samples from a latitudinal transect spanning 21–68° S. Phylogeographic, population genetic and molecular dating analyses were used to assess the demographic history of C. quitensis and the age of the species in Antarctica. Results Maritime Antarctic populations consisted of two different haplotype clusters, occupying the northern and southern Maritime Antarctic. Molecular dating analyses suggested C. quitensis to be a young ( Main conclusions. The Maritime Antarctic populations likely derived from two independent, late‐Pleistocene dispersal events. Both clusters shared haplotypes with sub‐Antarctic South Georgia, suggesting higher connectivity across the Southern Ocean than previously thought. The overall findings of multiple colonization events by a vascular plant species to Antarctica, and the recent timing of these events, are of significance with respect to future colonizations of the Antarctic Peninsula by vascular plants, particularly with predicted increases in ice‐free land in this area. This study fills a significant gap in our knowledge of the age of the contemporary Antarctic terrestrial biota. Adding to previous inferences on the other Antarctic vascular plant species (the grass Deschampsia antarctica ), we suggest that both angiosperm species are likely to have arrived on a recent (late‐Pleistocene) time‐scale. While most major groups of Antarctic terrestrial biota include examples of much longer‐term Antarctic persistence, the vascular flora stands out as the first identified terrestrial group that appears to be of recent origin.

Optimal designs for a linear-model compositional response - J. M. Rodríguez-Díaz; M. J. Rivas-López; M. T. Santos-Martín; I. Mariñas-Collado (Stochastic Environmental Research and Risk Assessment, 2020)

Palaeodietary reconstruction as an alternative approach to poorly preserved early medieval human bone assemblages: the case of Boadilla (Toledo, Spain) - Maite I. García-Collado; Paola Ricci; Raúl Catalán Ramos; Simona Altieri; Carmine Lubritto; Juan Antonio Quirós Castillo (Archaeological and Anthropological Sciences, 2019)

Impact of universal access to hepatitis C therapy on HIV-infected patients: implementation of the Spanish national hepatitis C strategy - A. Rivero-Juarez; L. F. Lopez-Cortes; M. Castaño; D. Merino; M. Marquez; M. Mancebo; F. Cuenca-Lopez; P. Jimenez-Aguilar; I. Lopez-Montesinos; S. Lopez-Cardenas; A. Collado; M. A. Lopez-Ruz; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Epicotyl sections as targets for plant regeneration and transient transformation of common bean using Agrobacterium tumefaciens - R. Collado; I. Bermúdez-Caraballoso; L. R. García; N. Veitía; D. Torres; C. Romero; G. Angenon (In Vitro Cellular & Developmental Biology - Plant, 2016)

Efficacy of and risk of bleeding during pegylated interferon plus ribavirin treatment in HIV/HCV-coinfected patients with pretreatment thrombocytopenia - J. A. Mira; K. Neukam; L. F. López-Cortés; A. Rivero-Juárez; F. Téllez; J. A. Girón-González; I. de los Santos-Gil; G. Ojeda-Burgos; D. Merino; M. J. Ríos-Villegas; A. Collado; A. Torres-Cornejo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Comparative genome analysis of Bacillus spp. and its relationship with bioactive nonribosomal peptide production - A. Hamdache; R. Azarken; A. Lamarti; J. Aleu; I. G. Collado (Phytochemistry Reviews, 2013)

Neuroprotective effect of carvedilol and melatonin on 3-nitropropionic acid-induced neurotoxicity in neuroblastoma - I. Tasset; C. Espínola; F. J. Medina; M. Feijóo; C. Ruiz; E. Moreno; M. M. Gómez; J. A. Collado; C. Muñoz; J. Muntané; P. Montilla; I. Túnez (Journal of Physiology and Biochemistry, 2009)

The Putative Role of Botrydial and Related Metabolites in the Infection Mechanism of Botrytis cinerea - A. J. Colmenares; J. Aleu; R. Durán-Patrón; I. G. Collado; R. Hernández-Galán (Journal of Chemical Ecology, 2002)

Production of antibacterial activities by members of the family Pseudonocardiaceae: influence of nutrients - G. Platas; R. Morón; I. González; J. Collado; O. Genilloud; F. Peláez; M.T. Diez (World Journal of Microbiology and Biotechnology, 1998)